2004
DOI: 10.1007/bf03033311
|View full text |Cite
|
Sign up to set email alerts
|

DRD2 TaqIA polymorphism is associated with urinary homovanillic acid levels in a sample of spanish male alcoholic patients

Abstract: The TaqIA1 allele of the dopamine receptor gene D2 (DRD2) has been associated with alcoholism, as well as with other addictive behaviours. The exact nature of how the presence of this allele can be a vulnerability factor in the development of alcoholism remains unclear. In this study we found that the presence in the DRD2 genotype of the TaqIA1 allele in Spanish alcoholics is associated with higher levels of urine homovanillic acid (HVA) when compared to patients homozygous for the TaqIA2 allele. A sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Lower D2S-autoreceptor functioning has been related to impaired autoregulatory modulation of TH and DAT activity in the striatum in response to DA release (impaired downregulation of TH or upregulation of DAT) (Dickinson et al, 1999;Håkansson et al, 2004). In accordance, the A1-allele, particularly when homozygous (A1/A1), leads to higher DA turnover and tonic activity as evinced by its association to increased aromatic L-amino acid decarboxylase (AAAD) activity, higher levels of [18F]FDOPA uptake in the striatum, higher urinary and cerebrospinal fluid HVA levels, and higher levels of DA release during gambling tasks (Jönsson et al, 1996;Ponce et al, 2004;Laakso et al, 2005;Joutsa et al, 2014). Nonetheless, one study failed to find an effect of the TaqIA-ANKK1 on HVA levels in violent alcoholics although long-term substance dependence could have skewed the results (Goldman et al, 1992).…”
Section: Da Receptor Configuration (D2-receptors)mentioning
confidence: 93%
“…Lower D2S-autoreceptor functioning has been related to impaired autoregulatory modulation of TH and DAT activity in the striatum in response to DA release (impaired downregulation of TH or upregulation of DAT) (Dickinson et al, 1999;Håkansson et al, 2004). In accordance, the A1-allele, particularly when homozygous (A1/A1), leads to higher DA turnover and tonic activity as evinced by its association to increased aromatic L-amino acid decarboxylase (AAAD) activity, higher levels of [18F]FDOPA uptake in the striatum, higher urinary and cerebrospinal fluid HVA levels, and higher levels of DA release during gambling tasks (Jönsson et al, 1996;Ponce et al, 2004;Laakso et al, 2005;Joutsa et al, 2014). Nonetheless, one study failed to find an effect of the TaqIA-ANKK1 on HVA levels in violent alcoholics although long-term substance dependence could have skewed the results (Goldman et al, 1992).…”
Section: Da Receptor Configuration (D2-receptors)mentioning
confidence: 93%
“…Notably, more recent studies have shown this polymorphism lies more than 10 kb downstream from DRD2 in an exon of a neighboring gene, ANKK1 (Neville et al 2004). Nonetheless, the TaqIA polymorphism remains an interesting polymorphism for studying DRD2 associations given that it has been related to DRD2 expression levels (Laakso et al 2005;Thompson et al 1997) and urinary levels of the dopamine metabolite homovanillic acid (Ponce et al 2004).…”
Section: Figmentioning
confidence: 99%
“…The PET studies show that the A1 allele is associated with reduced D2 autoreceptor density in vivo in human striatum (as measured by [ 11 C]raclopride) and a corresponding decrease in autoreceptor function (as measured by [ 18 F]FDOPA), accompanied by reduced mean relative glucose metabolic rate in the medial PFC and other brain regions. The suggestion that lower D2-receptor expression leads to decreased autoreceptor function is supported by an association of the DRD2 TaqIA A1 allele (TaqA1) with higher levels of urinary homovanillic acid (Ponce et al, 2004). Together, these data suggest that A1-allele carriers show poor dopaminergic function.…”
mentioning
confidence: 92%